Assessing the feasibility of creating tsetse and trypanosomosis-free zones. (23rd November 2017) - Feldmann, Udo; Leak, Stephen G. A.; Hendrichs, Jorge
Abstract: The establishment of the Pan-African Tsetse and Trypanosomosis Eradication Campaign (PATTEC) falling under the African Union Commission, and the initiation of national PATTEC projects in affected African countries stimulated a revival of national and sub-regional efforts and helped to generate donor support for creating sustainable agricultural and livestock development zones that are free of tsetse and trypanosomosis (T&T). Such projects are long-term, complex undertakings, requiring careful planning and consideration of relevant technical and non-technical interdependencies. There is international consensus that T&T interventions should: (a) adopt a phased and conditional approach in their planning, implementation, and monitoring; (b) adhere to the integrated pest management area-wide (AW-IPM) concept, ensuring that the most appropriate combination or sequence of intervention measures is selected; and (c) follow the AW-IPM concept of targeting entire isolated or well-confined insect pest populations. The phases of this process include: (a) policy and strategy development, assurance of long-term commitment, and establishment of effective management structures; (b) baseline data collection; (c) general technical feasibility assessment; (d) consideration of various relevant factors and trends; (e) detailed assessment of the technical feasibility of combinations of intervention tactics that may or may not include a sterile insect technique component; (f) capacity development and pre-operational work; (g) operational implementation of an AW-IPM campaign to create T&T-free zones; and (h) adherence to agreed procedures for the 'Declaration of Assumption of Freedom from T&T', and, eventually, the 'Declaration of Elimination'. This paper provides guidance on the steps to be followed to assess the feasibility of creating T&T-free zones.